Variable ventilation ages in the equatorial Indian Ocean thermocline during the LGM - Raddatz, Jacek; Beisel, Elvira; Butzin, M.; Schröder-Ritzrau, Andrea; Betzler, C.; Friedrich, Ronny; Frank, Norbert (Scientific reports, 2023)
Variations of atmospheric CO2 during the Pleistocene ice-ages have been associated with changes in the drawdown of carbon into the deep-sea. Modelling studies suggest that about one third of the glacial carbon drawdown may not be associated to the deep ocean, but to the thermocline or intermediate ocean. However, the carbon storage capacity of thermocline waters is still poorly constrained. Here we present paired 230Th/U and 14C measurements on scleractinian cold-water corals retrieved from ~ 450 m water depth off the Maldives in the Indian Ocean. Based on these measurements we calculate ∆14C, ∆∆14C and Benthic-Atmosphere (Batm) ages in order to understand the ventilation dynamics of the equatorial Indian Ocean thermocline during the Last Glacial Maximum (LGM). Our results demonstrate a radiocarbon depleted thermocline as low as -250 to -345‰ (∆∆14C), corresponding to ~ 500-2100 years (Batm) old waters at the LGM compared to ~ 380 years today. More broadly, we show that thermocline ventilation ages are one order of magnitude more variable than previously thought. Such a radiocarbon depleted thermocline can at least partly be explained by variable abyssal upwelling of deep-water masses with elevated respired carbon concentrations. Our results therefore have implications for radiocarbon-only based age models and imply that upper thermocline waters as shallow as 400 m depth can also contribute to some of the glacial carbon drawdown.
Gesehen am 14.11.2023